Telecommuting and transportation: relationship and implications - Kadar Hamsa, Abdul Azeez; Wan Mohd Rani, Wan Nurul Mardiah (IIUM Press, 2009)
This book studies to what extent telecommuting has replaced conventional commuting in Malaysia and discusses the resultant benefits. The authors’ analysis is based on a survey of workers in the information and related industries. The respondents were asked to state their preference between the two forms of telecommuting. Telecommuting is a new phenomenon in Malaysia, but has elsewhere become an important consideration in human resources management—particularly where it concerns workers in the information, communication and related industries—as well as in studies on traffic congestion in big cities. This work should benefit researchers, scholars, students, consultants, professionals and anyone whose work or interest concerns traffic and transportation, information and communication technology, business management and the built environment.